Bibliometric Analysis of Research Trends in Habituation-Based Programs to Enhance Moral Education in Primary Schools - Thufail Mujaddid Al-Qoyyim; Siti Maulidiya Nabila (Current Educational Review, 2025)
This bibliometric study investigates research trends in habituation-based programs designed to enhance moral education in primary schools. Using Dimensions AI as the primary database, supported by VOSviewer for visualization, the study analyzed 2016–2025 publications based on thematic keywords such as character, behavior, responsibility, and religious character. The results show a notable rise in publications since 2019, peaking in 2022, largely contributed by Indonesian scholars and journals. Dominant disciplines include Education and Philosophy/Religious Studies, reflecting the pedagogical and ethical foundations of habituation practices. Keyword analysis revealed strong focus on character formation, behavioral transformation, and the integration of moral values into daily school routines. Overlay visualization indicated a shift toward 21st-century skills and digital habituation, while density mapping highlighted underexplored areas such as multicultural values and virtual learning. The study identified key contributors, top journals, and keyword networks, revealing a dynamic yet uneven landscape in the academic exploration of habituation. Although substantial progress has been made, gaps remain in addressing pluralistic, secular, and technological contexts. Thus, future research should promote interdisciplinary collaboration, contextual adaptability, and broader international dissemination. By offering a comprehensive research map, this study contributes to the development of reflective, sustainable, and evidence-based moral education strategies that go beyond formal instruction and embed values through habitual practice